2020
DOI: 10.3390/w12082285
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Doped Cobalt Ferrite as an Efficient Photocatalyst for the Abatement of Methylene Blue

Abstract: The present study is aimed to access the photodegradation efficiency of methylene blue dye using CoFe2O4 and Co0.1Al0.03Fe0.17O0.4 nanoparticles. The synthesis of spinel ferrites nanoparticles was performed by a facile sol-gel method. The synthesized nanoparticles were characterized by FTIR, XRD, SEM, EDS, Nitrogen adsorption/desorption and UV–Visible spectroscopy. The XRD studies confirmed the spinel cubic structure of ferrite. It was also found that the crystallinity increases at an annealing temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Such a rational catalyst design provided exceptional OER performance by demonstrating 50 mA/cm 2 at a low overpotential of 265 mV. Abbas et al worked on synthesizing Al 3+ -doped CoFe 2 O 4 NPs using the sol–gel method . The photodegradation efficiency of Al 3+ -doped cobalt ferrite was recorded to be 83% for a 120 min light illumination, which was much better than that of an undoped sample (58%).…”
Section: Introductionmentioning
confidence: 99%
“…Such a rational catalyst design provided exceptional OER performance by demonstrating 50 mA/cm 2 at a low overpotential of 265 mV. Abbas et al worked on synthesizing Al 3+ -doped CoFe 2 O 4 NPs using the sol–gel method . The photodegradation efficiency of Al 3+ -doped cobalt ferrite was recorded to be 83% for a 120 min light illumination, which was much better than that of an undoped sample (58%).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enhancements in specic surface area have been noted with various aluminumsubstituted cobalt ferrites. [23][24][25] Scanning electron micrographs of calcined VFe 2 Ox and Al-VFe 2 Ox aerogels show that both oxides comprise highly porous and networked nanostructures (Fig. 2(a and b) and S2a, b †), but VFe 2 Ox has larger particles within its 3D solid network.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of aluminum-doped CoFe 2 O 4 catalytic degradation of MB, it was found that the microscopic morphology of the aluminum-doped catalyst was more uniform and ordered, and the specific surface area increased from 9.217 m 2 g −1 to 14.865 m 2 g −1 . 94 The lattice parameter decreases with Al insertion into the structure due to the replacement of the larger atomic Fe 3+ (0.67 Å) by the smaller atomic Al 3+ (0.51 Å). The final experiments show that Co 0.1 Al 0.03 Fe 0.17 O 0.4 has the highest photocatalytic activity.…”
Section: Methods To Improve the Photo-fenton Catalytic Performancementioning
confidence: 99%